2022
DOI: 10.1007/s11618-022-01089-w
|View full text |Cite
|
Sign up to set email alerts
|

What beliefs about writing guide EFL curricula? An analysis of relevant policy documents for teaching English at German secondary schools

Abstract: Although curricular analyses are of crucial importance for curricular development, documents for teaching writing in English as a foreign language [EFL] in Germany have not yet received much attention. Our study explores what beliefs about writing guide educational policy documents for teaching EFL in Germany. Using Ivanič’s (2004) discourses of writing [DoW] as a theoretical lens, we conduct a curricular analysis of 11 curricula for lower secondary school (Year 9/10) and their guiding superordinate documents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on research data, this study found that the use of synonyms of participating students was fluent, flexible, original, and detailed. Judging from fluency in the use of synonyms, students are classified as fluent (Kim et al, 2021;Peltzer et al, 2022). This fluency can be seen from the accuracy of the choice of terms that allow the concept of meaning contained in these terms to be able to form a unified meaning in the context of a sentence (Daris Hadianto et al, 2021;Peary, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on research data, this study found that the use of synonyms of participating students was fluent, flexible, original, and detailed. Judging from fluency in the use of synonyms, students are classified as fluent (Kim et al, 2021;Peltzer et al, 2022). This fluency can be seen from the accuracy of the choice of terms that allow the concept of meaning contained in these terms to be able to form a unified meaning in the context of a sentence (Daris Hadianto et al, 2021;Peary, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Writing is key for participating in political and societal discourses ( Peltzer et al, 2022 ), succeeding in school ( Graham and Perin, 2007 ), or finding adequate employment in the work sector ( National Commission on Writing, 2004 ; Cellier et al, 2007 ; Aschliman, 2016 ). Yet, many teenagers struggle with writing comprehensive texts and fail to reach a satisfactory level of writing proficiency (e.g., National Commission on Writing, 2004 ).…”
Section: Introductionmentioning
confidence: 99%